Improving the Push-Out Bond Strength of Fiber Posts in Diabetic Dentin: The Role of Chlorexidine Irrigation and Resin Cements - Beyza Arslandaş Dinçtürk; Arzu Şahin Mantı; Cemile Kedici Alp; Ayşenur Altuğ Yıldırım; Arzu Kaya Mumcu (Journal of Functional Biomaterials)
This study evaluated the effect of resin cements and post-space irrigation solutions on the push-out bond strength of diabetic and non-diabetic dentin. A total of 160 human central teeth (80 diabetic, 80 non-diabetic) were prepared using X5 files and obturated with AH Plus sealer and X5 gutta-percha. Post spaces were prepared, and teeth were divided into eight groups based on resin cements (Variolink N, Panavia SA Universal) and irrigation protocols (saline, saline + 2% CHX). A 1 mm slice from each tooth’s middle third was tested for push-out bond strength. Statistical analysis was performed using three-way ANOVA and Tukey HSD tests. In non-diabetic dentin, saline + CHX with Variolink N achieved the highest bond strength. In diabetic dentin, saline with Panavia SA Universal resulted in the lowest bond strength (p < 0.05). The dentin type, resin cement, and irrigation solution significantly impacted fiber post bond strength, and CHX irrigation improved it.